1998
DOI: 10.1046/j.1365-2222.1998.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic bacteria down‐regulate the milk‐induced inflammatory response in milk‐hypersensitive subjects but have an immunostimulatory effect in healthy subjects

Abstract: Probiotic bacteria appear to modulate the nonspecific immune response differently in healthy and hypersensitive subjects. This is seen as an immunostimulatory effect in healthy subjects, and as a down-regulation of immunoinflammatory response in milk-hypersensitive subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
11

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(130 citation statements)
references
References 35 publications
4
115
0
11
Order By: Relevance
“…This shows that the probiotic diet increases respiratory burst activity and complement activity in common carp. It has been shown that certain probiotic bacteria and triherbal extracts are able to stimulate phagocytic activity (Arunachalam et al 2000, Schiffrin et al 1997, Harikrishnan et al 2009) as well as complement receptor expression (Pelto et al 1998). Respiratory burst activity correlates well with phagocytosis of bacteria in fish (Hardie et al 1996, Neumann et al 2001 as well as in humans (Loimaranta et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the probiotic diet increases respiratory burst activity and complement activity in common carp. It has been shown that certain probiotic bacteria and triherbal extracts are able to stimulate phagocytic activity (Arunachalam et al 2000, Schiffrin et al 1997, Harikrishnan et al 2009) as well as complement receptor expression (Pelto et al 1998). Respiratory burst activity correlates well with phagocytosis of bacteria in fish (Hardie et al 1996, Neumann et al 2001 as well as in humans (Loimaranta et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In this process, it needs to be taken into account that the response to probiotic supplementation depends on the immunological status of the host, as demonstrated by in vitro 98,199 and in vivo experiments. 168,200 What ultimately counts in the search for functional foods to modulate the immune response is that well-tolerated and effective nutrients are needed, and probiotics are currently among the best candidates to play this critical role in future epidemics of metabolic and infl ammatory conditions.…”
Section: Final Comments and Thoughtsmentioning
confidence: 99%
“…19 In addition, it has been suggested that Lactobacillus exerts an anti-inflammatory effect in milk-hypersensitive children as a result of downregulation of the immunoinflammatory response. 20 The second aim of this pilot study was to test the hypothesis that the administration of probiotics reduces intestinal inflammation in CF.…”
Section: Introductionmentioning
confidence: 99%